Assessment of Heavy Metals Uptake by Vegetables Cultivated on Soil Receiving Industrial Wastewater in Minna, Nigeria - Adeoye, P. A.; Saidu, Z.; Kuti, A. I.; Ibrahim, J.; Adabembe, B. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Consumption of vegetable crops grown on soil irrigated with industrial wastewater has been the order of the day in most urban towns and cities of Nigeria, despite reports of its serious health impact. This study assessed the possibility of uptake of heavy metals by crops grown on soil receiving industrial wastewater during rainy and dry seasons. The crops investigated are Spinach, Cayenne Pepper, Jute mallow, roselle and lady’s fingers okra. The initial composition of the wastewater was analyzed to contain 0.89 mg/l of chromium, 0.74 mg/l of cadmium, 1.04 mg/l of copper and 2.81 mg/l of iron. Control water used for this experiment contain no trace of any of these heavy metals. The experimental soil was also analyzed and contained 0.10 mg/kg of chromium, 0.06 mg/kg of iron before irrigation in dry season. After irrigation at the wastewater plots, the heavy metal concentrations in soil had increased to 6.24 mg/kg of chromium and 7.50 mg/kg of iron. In wet season, the concentrations of heavy metals in the soil were 0.00 mg/kg of chromium and 2.32 mg/kg of iron before irrigation. After irrigation in wet season, the concentrations increased to 6.01 mg/kg of iron. Mean difference of heavy metal concentrations were significantly high in vegetables in dry season, with values ranging from 0.03 mg/kg to 211mg/kg in wastewater plots, 0.20 mg/kg to 215 mg/kg in wet seasons wastewater plots, 0.00 mg/kg to 157 mg/kg in dry season. It is however recommended that consumption of vegetables irrigated with domestic/industrial wastewater be strongly discouraged because of its serious health implications.